2013
DOI: 10.1080/15389588.2013.867483
|View full text |Cite
|
Sign up to set email alerts
|

Child Restraint Use in Canadian Provinces With and Without Legislation in 2010

Abstract: The findings from this study suggest that child safety seat legislation has an impact on restraint use in Canada. Despite the increase in rates of child safety seat use in provinces with new legislation and stable rates in provinces with old legislation, use rates remain low. Injury prevention strategies including further surveillance, interventions, and enforcement of restraint use in children are important to decrease motor vehicle related injury and death.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 7 publications
3
13
0
Order By: Relevance
“…Stricter federal impaired driving laws and improved enforcement over the study period could have further contributed to reduced MVC rates 29 . In addition, the increased use of child safety seats and recent introduction of child safety seat legislation in Canada could account for the decline in MVC rates among young children 30 . These results, while encouraging, underscore the need for continued injury prevention targeted to children and young adults, who remain the most at risk for hospitalization from MVCs.…”
Section: Discussionmentioning
confidence: 99%
“…Stricter federal impaired driving laws and improved enforcement over the study period could have further contributed to reduced MVC rates 29 . In addition, the increased use of child safety seats and recent introduction of child safety seat legislation in Canada could account for the decline in MVC rates among young children 30 . These results, while encouraging, underscore the need for continued injury prevention targeted to children and young adults, who remain the most at risk for hospitalization from MVCs.…”
Section: Discussionmentioning
confidence: 99%
“…In Canada, Simniceanu et al (2013) [27] concluded that the legislation has an impact on restraint use. Despite the increased number of parents that carry children in these devices, the use rates in the population studied remained low.…”
Section: Resultsmentioning
confidence: 99%
“…Child passenger safety laws have been well implemented and enforced in the United States and other European countries for many years [7,10,22,23,24]. In the US, CSS laws have been enacted for more than two decades, and the usage of CSS was 98% among infants and 89% among children age 1 to 3 in 2006 [25].…”
Section: Discussionmentioning
confidence: 99%
“…In 2000, Japan’s Road Traffic Law stipulating CSS use among children aged 0–5 years went into effect, while, in China, even today there is no national legislation [9]. To increase CSS use following hospital discharge and improve the knowledge of parents, many intervention programs have been implemented, including CSS education, CSS installation training, CSS discharge polices of newborns and CSS laws, all of which showed success in increasing CSS use [10,11,12,13,14,15,16,17,18,19]. A published review in 2001 showed that more than 10 programs included the strategies of providing free loaner CSS, giveaways or low-cost rentals to the parents of children, in addition to educational components such as instruction or written materials, professional installation training, or rehearsal of skills [20].…”
Section: Introductionmentioning
confidence: 99%